Building a Medical Undergraduate Palliative Care Curriculum: Lessons Learned. Issue 1 (January 2021) - Bush, Shirley H.; Gratton, Valérie; Kabir, Monisha; Enright, Paula; Grassau, Pamela A.; Rice, Jill; Hall, Pippa
Previous literature demonstrates that current palliative care training is in need of improvement for medical students in global, European and Canadian contexts. The training of medical undergraduates is key to ensure that the ongoing and increasing need for enhanced access to palliative care across all settings and communities is met. We describe building a comprehensive palliative and end-of-life care curriculum for medical undergraduates at our university. As with recent European and US studies, we found that the process of university curriculum renewal provided a critical opportunity to integrate palliative care content, but needed a local palliative care champion already in place as an energetic and tireless advocate. The development and integration of a substantive bilingual (English and French) palliative and end-of-life care curriculum over the 4-year medical undergraduate program at our university has occurred over the course of 14 years, and required multiple steps and initiatives. Subsequent to the development of the curriculum, there has been a 13-fold increase in students selecting our palliative care clinical rotations. Critical lessons learned speak to the importance of having a team vision, interprofessional collaboration with a focus on vision, plans and implementation, and flexibility to actively respond and further integrate new educational opportunities within the curriculum. Future directions for our palliative care curriculum include shifting to a competency-based training and evaluation paradigm. Our findings and lessons learned may help others who are working to develop a comprehensive undergraduate medical education curriculum.